EMOTIONAL INTELLIGENCE AND GENDER DIFFERENCE IN ELEMENTARY SCHOOL: A SYSTEMATIC LITERATURE REVIEW - Tria Monica; Muhammad Solehuddin; Sudaryat N. Akhmad (Universitas Pendidikan Indonesia, 2021)
Emotional intelligence refers to a person's ability to manage and control his emotions and to have the ability to control other people's feelings as well. The article is serving intelligence emotional and differences of gender in children age school basis. This article sheds light on how intelligence is. Dynamic views of gender will be discussed more further in the report. The paper used in the article is that a systematic literature review to examine journals from 7 databases of 150 journals is eight journals that meet the criteria to be identified by the study. The results obtained from this study show that there is a significant difference between the level of emotional intelligence of students based on gender